The Impact of Leader's Authority and Work Fulfillment on Work Performance - Syamsuddin, Rahmi Andini; Fahmi Susanti (International Journal of Indonesian Business Review, 2023)
Purpose – The purpose of this study was to determine and analyze the impact of Leaders authority and work fulfillment on work performance in South Tangerang District Methodology/approach – The method used is descriptive quantitative with an associative approach. The population of all employees in South Tangerang District, the sample is 67 people, the technique of the sample is saturated. Findings – It was found that. The result of this research is that Leaders authority has a significant effect on work performance with 0,994 correlation coefficient value. there is a simultaneous significant impact between Leaders authority and work fulfillment on work performance in South Tangerang District Novelty/value – This research focus on Work Performance that influenced by leaders authority and work performance. Based on the results of the analysis, it was found that these two variable have the same strong impact.